Isolation and Molecular Detection of Fowl Adenovirus causing Inclusion Body Hepatitis utilizing Specific Pathogen- Free Embryonated Chicken Eggs - Tikoo, Mehak; Warke, Shubhangi; Sonkusale, Prashant; Fulsundar, Rohan (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Indian poultry industry is rapidly growing with an increase in demand among consumers, thus, prevailing control and prevention  measures of poultry diseases need to be improved along with the implementation of efficient disease diagnostics. Fowl adenovirus  (FAdV) is responsible for causing inclusion body hepatitis (IBH) in broiler chickens, incurring huge economic losses in the poultry  industry. A total of 11 pooled liver homogenate samples from an outbreak of IBH in a poultry farm of Katol near Nagpur were collected  and processed by conventional PCR based on the detection of hexon gene and isolation in SPF embryonated chicken eggs. Out of  11 samples, 05 (45.45%) were found to be positive for FAdV by PCR. Inoculated embryos were haemorrhagic with prominent lesions  in the liver. All the viral isolates showing characteristic pathological lesions were detected positive by PCR. Histopathology revealed  basophilic intranuclear inclusion bodies in the liver of infected embryos. Continuous surveillance of FAdVs in broiler chicken flocks is  necessary for early detection of diseases.
Keywords: Chorioallantoic membrane (CAM); Chicken embryonated eggs; Hexon gene; Histopathology; nclusion body hepatitis